The Effect of Proactive Personality and Locus of Control on Innovative Work Behavior: the Mediating Role of Work Engagement - Tekeli, Mehmet; Özkoç, Aziz Gökhan (Anais Brasileiros de Estudos Turísticos, 2022)
The aim of the study is to test the mediating role of work engagement on the effects of proactive personality and locus of control characteristics on innovative work behaviors of the employees. A field study was conducted, and the research data were collected using the questionnaire technique for an empirical analysis of the structural equation modeling created for this purpose. The research population has consisted of employees working in food and beverage departments of hotel businesses, where complex and complicated activities are carried out, therefore a high amount of qualified workforce is needed. According to the results obtained in the results of the survey applied to the employees who provide services in the food and beverage department of the hotels located in Antalya province, which is one of the most important tourist destinations in Turkey. Employees’ proactive personality characteristics and their level of commitment positively affect their tendency to show innovative entrepreneurial behavior; proactive personality and internal locus of control had a positive and significant effect on work engagement; however, the mediating effect of external locus of control on innovative entrepreneurial behavior was not detected as significant.